The influence of geopathic zones on the psychophysiological state of the driver - Степанов, Алексей Викторович (Eastern-European Journal of Enterprise Technologies, 2010)
The interrelation of space factors with the geophysical anomalies was shown, existing in circumterraneous space, and also on certain depth inthe Earth’s mantle which have damaging an effect on a psychophysiological condition of the person, as the participant of traffic.